2018
DOI: 10.5194/hess-2018-467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sediment budget analysis of the Guayas River using a process-based model

Abstract: Abstract. The Equatorial Daule and Babahoyo rivers meet and combine into the tidal Guayas River, which flows into the largest estuary on the Pacific coast of South America. The city of Guayaquil, located along the Guayas, is the main port of Ecuador but, at the same time, the planet's fourth most vulnerable city to future flooding due to climate change. Fluvial sedimentation, which has increased in the recent years, is seen as one of the factors contributing to the risk of flooding. The planning and design of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…We evaluated the model's sensitivity to this parameter by varying the eddy viscosity between 0.1 and 1 m 2 /s and found that a value of 1 m 2 /s provided the closest agreement with measured velocities. While this value is high it is within the range of values reported in the literature for Delft3D‐FM models (Barrera Crespo et al., 2019; Martyr‐Koller et al., 2017; Willemsen et al., 2022). The specified eddy viscosity value maintained model stability and successfully reproduced the flow fields.…”
Section: Methodssupporting
confidence: 81%
“…We evaluated the model's sensitivity to this parameter by varying the eddy viscosity between 0.1 and 1 m 2 /s and found that a value of 1 m 2 /s provided the closest agreement with measured velocities. While this value is high it is within the range of values reported in the literature for Delft3D‐FM models (Barrera Crespo et al., 2019; Martyr‐Koller et al., 2017; Willemsen et al., 2022). The specified eddy viscosity value maintained model stability and successfully reproduced the flow fields.…”
Section: Methodssupporting
confidence: 81%
“…Upstream erosion lowers water quality and leads to siltation and associated flooding downstream (Barrowclough et al., 2016; Barrera Crespo et al., 2019; Restrepo & Escobar, 2018; Rosas et al., 2020). Climate change will not only affect the sustainability of soils in the higher elevations but will also impact lower elevation areas, where siltations will reduce water storage and create greater potential for flooding (Barrera Crespo et al., 2019).…”
Section: Global Challenges To Food Securitymentioning
confidence: 99%
“…Water runoff from Andean highland farming areas feeds some of the larger river systems draining into the Pacific Ocean. For example, the Chimbo river watershed in highland Ecuador provides about 40% of the water to the Guayas River, undoubtedly the most economically important river system in Ecuador as it serves as a source of water for industries, large cities, and agriculture; provides a means of transport; and flows to the Gulf of Guayaquil, which is the largest estuarine ecosystem on the Pacific coast of South America (Barrera et al., 2012; Barrera Crespo et al., 2019). Upstream erosion lowers water quality and leads to siltation and associated flooding downstream (Barrowclough et al., 2016; Barrera Crespo et al., 2019; Restrepo & Escobar, 2018; Rosas et al., 2020).…”
Section: Global Challenges To Food Securitymentioning
confidence: 99%
See 1 more Smart Citation